3D printing of cholesteric liquid crystal elastomers for optical sensors - Liow, Wei Jun (Nanyang Technological University, 2024)
Structural colouration offers some advantages over dyes and pigments. Structural colours are more durable and resistant to fading compared to dyes that may fade over time due to exposure to heat and light. Structural colours can also exhibit unique optical effects, such as iridescence, that conventional dyes are not capable of producing. Cholesteric liquid crystal elastomers (CLCEs) are a type of material that exhibits structural colouration and has great potential in applications such as strain sensors, anti-counterfeiting measures, bioinspired camouflage, and soft machines. However, CLCEs fabricated through conventional methods have limited potential. Hence, there is great research interest in the use of three-dimensional (3D) printing for the fabrication of CLCEs. Since 3D printing of CLCEs is relatively new, there was a need to investigate the mechanical properties of optimised ink and printing parameters. To understand the mechanical properties of CLCEs that were synthesised by 3D printing, tensile tests were conducted to see if the material performs well. Printing parameters were varied to find optimal optical properties while maintaining acceptable mechanical properties. The results showed the potential of the 3D-printed CLCE being used as optical strain sensors.